Mediation as a ‘Nothing to Lose’ Mode for Alternative Mode of Dispute Resolution in Construction Works - Kamarudin, Abdul Rani (LexisNexis Malaysia Sdn Bhd, 2011)
In any dispute whether it is between entrepreneurs or otherwise, the court would seem to be the final adjudicator as to who is right and who is in the wrong. In other words, the party at fault will lose, pay damages and cost to the winner. One way or another, the time taken needed to know the outcome of the dispute, often than not, is too long and too slow, and can even be a painful experience even for the winner. Of late, arbitration has taken quite a dynamic leap as to how disputing parties resolve their disputes. This could have been due to the considerable considerable time taken by courts to come to an ultimatum on the disputing parties’ obligations, or could also be due to parties unwittingly have arbitration as a standard clause in their contract in the event of any dispute. For hundreds of years it has been accepted that litigation was the way to solve disputes. Arbitration came along to find an alternative. While arbitration as an alternative dispute resolution has been gaining grounds, and disputing parties select the arbitrator of their choice, it is basically no different from a court, as once the parties submit to arbitrate their case before an arbitrator (quasi-judicial), their fate is either win or lose, and parties relation may be severed beyond repair. This process too has been found to be costly, prolonged and may perhaps only be more appropriate for commercial disputes. It is still a win lose situation not a win-win situation with the disputing parties having no say as to how they should resolve their disputes. In short, litigation in the courts or arbitration proceedings is costly, time-consuming with unpredictable outcomes and above all, the ‘winner takes all’ and this, inevitably, has the potential to damage irreparably the relationships between the parties, for example, in matrimonial and labour disputes, among others. This paper is on mediation, an effective and affordable complement to litigation. Mediation may be opted for in a wide range of subject matters, such as in civil and commercial disputes, matrimonial, personal injury, environmental and labour disputes, among others. It is as a nothing to lose alternative dispute resolution, and why disputing parties should resort to it as their first option, and for them to determine for themselves how their disputes should be resolved particularly so for disputes in construction projects where disagreements must be resolved as quickly as possible to meet the project time line.